1988
DOI: 10.1039/an9881301837
|View full text |Cite
|
Sign up to set email alerts
|

Accurate measurement of stable isotopes of magnesium in biological materials with inductively coupled plasma mass spectrometry

Abstract: A method is described for the accurate isotopic determination of magnesium (24M9, *5Mg, 26Mg) in biological materials, which is based on inductively coupled plasma mass spectrometry (ICP-MS). The analytical performance of the method was examined with respect to the requirements of stable isotope tracer studies. When applied to the measurement of base-line isotope ratios (MR, , b) in rat tissue the following results were obtained (data are given in terms of MR25p4 and MR2~24 f IRSD, n = 4 or 5): standard soluti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
18
0

Year Published

1989
1989
2015
2015

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 35 publications
(18 citation statements)
references
References 1 publication
0
18
0
Order By: Relevance
“…Isotope ratio measurements were obtained with ICP-MS using an Elan Model 250 system (SCIEXIPerkin Elmer, Norwalk, CT). We have recently demonstrated that measurement precision (%CV) for the isotope pairs 25Mg/24Mg and 26Mg/ 24Mg with this method is in the range of 0.1-1 % for a number of different biologic matrices (6).…”
Section: Icp-ms Inductively Coupled Plasma Mass Spectrometrymentioning
confidence: 99%
See 2 more Smart Citations
“…Isotope ratio measurements were obtained with ICP-MS using an Elan Model 250 system (SCIEXIPerkin Elmer, Norwalk, CT). We have recently demonstrated that measurement precision (%CV) for the isotope pairs 25Mg/24Mg and 26Mg/ 24Mg with this method is in the range of 0.1-1 % for a number of different biologic matrices (6).…”
Section: Icp-ms Inductively Coupled Plasma Mass Spectrometrymentioning
confidence: 99%
“…Serum, urine, and fecal samples were prepared for isotopic analysis as described previously (6). Isotope ratio measurements were obtained with ICP-MS using an Elan Model 250 system (SCIEXIPerkin Elmer, Norwalk, CT).…”
Section: Icp-ms Inductively Coupled Plasma Mass Spectrometrymentioning
confidence: 99%
See 1 more Smart Citation
“…New generations of mass spectrometers with improved accuracy and requiring smaller doses of isotopes to be administered have been developed, but sample preparation remained time consuming (4)(5)(6). The development of inductively coupled plasma mass spectrometry (ICP-MS) brought about higher sensitivity, rapid throughput, and less time-consuming sample preparation, simplifying magnesium isotopic ratio measurements (7).…”
Section: Introductionmentioning
confidence: 99%
“…In addition to the radioactive isotopes, three stable Mg 2ϩ isotopes exist. These stable isotopes, i.e., 24 Mg, 25 Mg, and 26 Mg, have a respective natural abundance of 79, 10, and 11% and can be distinguished by inductively coupled plasma mass spectrometry (ICP-MS) (39) …”
mentioning
confidence: 99%